Tamsa, renaturalización de la calle 26 (2020)
TAMSA, is a project with different complexities such as the different scales of affectation that vary from the sectoral to the regional, or the multiple dynamics present in the territory. It is a public space design project, on the axis of Calle 26 in Bogotá from Carrera 68 to Avenida NQS or Carrera 30, for the implementation of the project is researched on the environmental history of Bogotá and the urban history of Calle 26, under the concept of renaturalisation what is sought is the conformity of a sustainable urbanism on the areas of affluence of the project, since it seeks to strengthen the ecosystem relations of the territory and the ecological resilience on the soil. In addition to the implementation of different intervention criteria such as accessibility, continuity and permeability, safety and comfort, identity and sustainability, social and artistic aspects on the axis are taken into account so that the population in general, have a total use of the public space and be appreciated the different artistic expressions on the axis of the Street 26 as they are the sculptures and the murals present on the way.